Ai margini della saga: Finnar, profezie e visioni nella Vatnsdæla saga - Nicola Martellozzo (2020)
This article aims to analyze the description of the soul-journey made by the Finnar in the Vatnsdæla saga, considering shamanic interpretation as a problematic category. Scandinavians and Finno-Ugric peoples have shared Fennoscandia for centuries, and their intercultural contacts influenced the representation of Finnar in Icelandic sagas. These historical relations had left several marks on the Norse literary imaginary, starting from the description of the magic techniques of Finnar. Many of these medieval practices were interpreted by scholars through shamanism, relying on the cultural continuity between Finnar and Sámi. This approach can be applied also to the soul-journey depicted in the Vatnsdæla saga, especially when compared with other similar episodes of Norwegian and Icelandic folklore. However, the perspective and the modalities of the travel are quite different from that of the Sámi shamanism, reflecting instead the Norse categories of magic, used to explain the supernatural abilities of the Finnar